Differentiated thyroid carcinoma referred for radioiodine therapy - Al-Balawi, Ibrahim A.; Meir, Hadir M.; Yousef, Mohammed K.; Nayel, Hala A.; Al-Mobarak, Mohammed F. (Saudi Medical Journal, 2001)
OBJECTIVE: The current work was conducted to study the disease status and treatment results of patients with differentiated thyroid carcinoma referred for radioactive iodine therapy.METHODS: Retrospective review of 78 patients with differentiated thyroid carcinoma referred for radioiodine therapy in the Nuclear Medicine Unit, King Abdulaziz Hospital and Oncology Center, Jeddah, Kingdom of Saudi Arabia. Analysis of the clinicopathologic characteristics, age correlation to different risk factors, treatment protocol and results were performed.RESULTS: Seventy seven percent were female and the female to male ratio was 3.5:1. The age of patients ranged between 13-63 years with a median age of 36 years. Cervical lymph node involvement was detected in 22 patients (25%). Papillary carcinoma was encountered in 78 patients (90%) and follicular carcinoma in 9 patients (10%). Analysis of the clinicopathologic characteristics showed no statistically significant difference between patients in the different age groups except for extrathyroid extension and lymph node involvement. Patients older than 45 years had a statistically significant lower incidence of nodal involvement and higher incidence of extra thyroid extension (P<0.02). In the current study we used a high dose method (Radioiodine-131 dose 75-100mCi) for thyroid remnant ablation after thyroidectomy (total or near total) in 67 patients. An Iodine 131 dose of 150 mCi was used in 12 patients with radioiodine-avid cervical lymph nodes and in 3 patients with gross residual tumor. In 4 patients with distant metastases an Iodine 131 dose of 200 mCi was used. For the whole study group the 5 year overall survival and disease-free survival was 96% and 88%.CONCLUSION: The current study, as with many other retrospective studies, concluded that despite the fact that differentiated thyroid carcinoma is among the most curable cancers, some patients are still at high risk for recurrent disease and associated mortality.